1994
DOI: 10.1063/1.870733
|View full text |Cite
|
Sign up to set email alerts
|

Filamentary double layers

Abstract: The properties of double layers produced in current filaments have been studied. The experiments were performed in a magnetized triple plasma device in which the diameter of the central plasma column could be varied. The scaling of the double layer potential drop V dl with the parameter jd 2 , where j is the current density in the double layer and d is the double layer thickness, was determined for several values of the current filament radius Ro. For relatively large values of R o , the one-dimensional (Langm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Similar DP and TP configurations can be obtained by using apertures rather than grids (Torven 1982, Torven et al 1985, Merlino and Loomis 1990. Filamentary DLs have been studied in TP devices using a variable aperture (Theisen et al 1994). The plasma source can be a heated cathode plasma column rather than a hot filament discharge (Plamondon et al 1988, Lindberg 1992, Volwerk 1993.…”
Section: Anode Double Layer Devicesmentioning
confidence: 99%
“…Similar DP and TP configurations can be obtained by using apertures rather than grids (Torven 1982, Torven et al 1985, Merlino and Loomis 1990. Filamentary DLs have been studied in TP devices using a variable aperture (Theisen et al 1994). The plasma source can be a heated cathode plasma column rather than a hot filament discharge (Plamondon et al 1988, Lindberg 1992, Volwerk 1993.…”
Section: Anode Double Layer Devicesmentioning
confidence: 99%
“…It is also of interest to investigate a process which has been proposed to give low-frequency amplitude modulations of the HF waves excited at a double layer, namely Langmuir collapse [19]. Langmuir collapse is a nonlinear process in which waves are trapped within a density cavity.…”
Section: Comparison With Theorymentioning
confidence: 99%
“…In particular, the axial profiles of the plasma potential show that a DL is generated near the inlet of z = 0 at all oxygen gas concentrations. It was found that the outline of the DL was curved for O 2 gas concentrations of 5 and 10% by the proposed scaling of the DL potential drop [39,40]. In plasma processing applications, structured electrodes can be used to enhance the plasma density, the ion and the radical fluxes to the wafer.…”
Section: Discussionmentioning
confidence: 99%
“…where ε 0 , m and e are the vacuum permitivity, the mass and electric charge of electrons, respectively. In equation ( 1), the positive exponent r takes the value 2/3 for the plane DL and decreases as the DL curvature increases [39]. According to equation ( 2) and the current density j estimated from [40], the numerical values of the exponent are r = 0.19 and r = 0.03 for O 2 concentrations of 5% and 10%, respectively.…”
Section: Axial Structures Of Plasma Parameters At Various Oxygen Gas ...mentioning
confidence: 99%
See 1 more Smart Citation